2019
DOI: 10.1097/opx.0000000000001439
|View full text |Cite
|
Sign up to set email alerts
|

Clear and Single Binocular Vision in Near 3D Displays

Abstract: SIGNIFICANCE Accommodation/convergence mismatch induced by 3D displays can cause discomfort symptoms such as those induced by accommodation/convergence mismatch in clinical vergence testing. We found that the limits of clear and single vision during vergence tests are very different between 3D and clinical tests. Clinical vergences should not be used as substitutes for measures of vergences in 3D displays. PURPOSE The purposes of this study were to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…In previous research [3][4][5][6][7] , before measuring visual parameters, use immersive VR equipment for at least 30 min, so it is not meaningful to compare with it. The results of the accommodation test revealed that the AA of the participants' eyes decreased after using VR glasses to watch a 3D video.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous research [3][4][5][6][7] , before measuring visual parameters, use immersive VR equipment for at least 30 min, so it is not meaningful to compare with it. The results of the accommodation test revealed that the AA of the participants' eyes decreased after using VR glasses to watch a 3D video.…”
Section: Discussionmentioning
confidence: 99%
“…Factors exerting short-term effects include food or fluid intake, changes in systemic blood pressure, and vigorous physical activity. Although most factors affecting IOP are random and inherently unstable 11 , the resulting short-term effects are observable for a limited period.In previous studies, the effects of immersive VR devices on visual parameters are all focused on the visual effects after 30 min of use [3][4][5][6][7] . However, it takes about 10 min to get into immersion using VR mobile devices.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these two images, the human brain calculates the depth information of the scene [1]. A binocular vision system includes two cameras placed in parallel using different views to capture two images in order to obtain the depth information [2,3]. There are three kinds of stereoscopic display technology based on the principle of binocular parallax.…”
Section: Introductionmentioning
confidence: 99%